2017
DOI: 10.7554/elife.29215
|View full text |Cite
|
Sign up to set email alerts
|

Non-synaptic signaling from cerebellar climbing fibers modulates Golgi cell activity

Abstract: Golgi cells are the principal inhibitory neurons at the input stage of the cerebellum, providing feedforward and feedback inhibition through mossy fiber and parallel fiber synapses. In vivo studies have shown that Golgi cell activity is regulated by climbing fiber stimulation, yet there is little functional or anatomical evidence for synapses between climbing fibers and Golgi cells. Here, we show that glutamate released from climbing fibers activates ionotropic and metabotropic receptors on Golgi cells through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 83 publications
(135 reference statements)
0
27
0
Order By: Relevance
“…The change in membrane potential following Kiss1 ARH stimulation was significantly different between POMC and NPY/AgRP neurons ( Figure 7F ). Therefore, high-frequency activity in Kiss1 ARH neurons, which through presumably glutamate spillover to extrasynaptic mGluRs ( Nietz et al, 2017 ; Watanabe and Nakanishi, 2003 ), excites POMC but inhibits NPY/AgRP neurons.…”
Section: Resultsmentioning
confidence: 99%
“…The change in membrane potential following Kiss1 ARH stimulation was significantly different between POMC and NPY/AgRP neurons ( Figure 7F ). Therefore, high-frequency activity in Kiss1 ARH neurons, which through presumably glutamate spillover to extrasynaptic mGluRs ( Nietz et al, 2017 ; Watanabe and Nakanishi, 2003 ), excites POMC but inhibits NPY/AgRP neurons.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, PN injections labeled large GAD67-GFP1 neurons in the granule layer (presumed Golgi cells), which are known to receive synaptic input from PN mossy fiber afferents (Kanichay and Silver, 2008), and we observed MLI and presumed Golgi cell labeling following injections into the IO. In the latter case, these two cell types have been shown to be functionally coupled to olivary afferents through non-classical synaptic connections (Schulman and Bloom, 1981;Szapiro and Barbour, 2007;Xu and Edgley, 2008;Coddington et al, 2013;Nietz et al, 2017). For example, in slice recording experiments, Nietz et al (2017) observed short-latency EPSCs in Golgi neurons following optogenetic activation of olivary axon terminals.…”
Section: Transsynaptic Spread Of Aav1mentioning
confidence: 99%
“…Our results show that these early synaptic currents display properties of spillover, a mode of signaling that does not require anatomically-defined synapses but is facilitated by a high density of release sites where transmitter pooling between sites activates extrasynaptic or neighboring synaptic receptors ( Kullmann, 2000 ). Spillover-mediated signaling is prominent at specialized synapses in the cerebellum, where it can occur between neighboring cells even in the absence of anatomically-defined synaptic contacts ( Rossi and Hamann, 1998 ; Szapiro and Barbour, 2007 ; Coddington et al, 2013 ; Coddington et al, 2014 ; Nietz et al, 2017 ). Since anatomically-defined synaptic specializations and close appositions have been reported between PVs and retroviral-labeled DG progenitors, an alternative possibility is that slow GPSCs are generated at functionally immature synapses ( Song et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%